An all-in-one endoluminal acoustofluidic system enables spatiotemporal transmucosal drug delivery and barrier repair for inflammatory bowel disease - Yichen Liu; Xiaoming Zheng; Yang Qin; Jing Han; Zhiwei Cong; Shu Fan; Yan Li; Ruochen Wang; Xiaolong Guo; Qichao Huang; Xunan Jing; Yibo Liu; et al. (Chemical Engineering Journal, 2026)

Probabilistic assessment of post-earthquake running safety threshold for high-speed railway bridge based on nonparametric copula method - Yan Zhang; Guangsong Song; Hui Jiang; Junjun Guo; Qikai Sun; Yun Shan (Soil Dynamics and Earthquake Engineering, 2026)

Disruption of BnPHT5;1b gene enhances arsenate tolerance through increased arsenate retention in shoot cell walls of Brassica napus - Bei Han; Aosheng Jiang; Junjun Yan; Tao Wu; Bingbing Zhang; Yajie Wang; Xinyu Yang; Sheliang Wang; Zhuqing Zhao; Lei Shi (Journal of Hazardous Materials, 2026)

A soybean EIN transcription factor confers resistance to Phytophthora sojae and favorable agronomic traits - Meng Liu; Jiaxin Yin; Xudong Wei; Junjun Song; Yaqun Dongye; Xi Chen; Xin Fang; Xinyue Yu; Yan Sun; Jihao Ju; Xiaoyu Chen; Junjiang Wu; et al. (Plant Cell Reports, 2026)

Causal relationships between alzheimer’s disease genetics and brain connectivity alterations: a multi-modal mendelian randomization study with transcriptomic validation of 191 rs-fMRI and 635 DTI neuroimaging traits - Junjun Ji; Zhifan Li; Abao Xing; Gang Luo; Xiaobing Zhai; Wei Xu; Junrong Li; Tao Tan; Ruihong Jia; Yan Yan; Xianbin Zhang; Long Wang; et al. (Brain Imaging and Behavior, 2026)

Effects of foundation types on structural response to tunnelling in sand: A numerical investigation - Jingmin Xu; Zehui Yu; Yan Li; Junjun Ni (Computers and Geotechnics, 2026)

Integrating multi-stage interventions for harmful algal blooms effective management - Zhuwu Jiang; Jianxin Pan; Chengchun Shi; Xiao Yao; Huang Yu; Junjun Wang; Junjun Chen; Jyunhong Shen; Hai Yu; Wuqiang Zeng; Junlan Chen; Zhihao Lin; et al. (Journal of Environmental Management, 2026)

Exploring diverse physical technologies for microbial inactivation and toxin degradation in rice: A comprehensive review - Bengang Wu; Chenyu Song; Yiting Guo; Lei Cong; Junjun Dai; Shenao Nan; Yan Shen; Haile Ma (Food Control, 2026)

Impact of observation and surrogate-model noises on deep learning-based subsurface heterogeneous structure identification through monitoring network optimization - Yuzhou Xia; Chuanjun Zhan; Zhenxue Dai; Jichun Wu; Xiaoying Zhang; Huichao Yin; Jiahe Yan; Junjun Chen; Zihao Wang; Mohamad Reza Soltanian; Kenneth C. Carroll (Advances in Water Resources, 2026)

Enhancing drying behavior and textural properties of carrot slices by infrared drying combining contact ultrasound - Bengang Wu; Chenyu Song; Yiting Guo; Kun Gao; Ningning Ouyang; Shenao Nan; Junjun Dai; Yan Shen; Haile Ma (Food and Bioproducts Processing, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

The effects of dietary astaxanthin on the intestinal microbiota and metabolites, antioxidant capacity, and resistance to Decapod iridescent virus 1 in Macrobrachium rosenbergii - Cui Liu; Qiusheng Jing; Li Wang; Qincheng Huang; Yukun Jie; Yutong Zheng; Tiantian Ye; Junjun Yan; Zhimin Gu (Fish & Shellfish Immunology, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Ni-doped CdO/CdSe in-situ heterojunctions: Tunable composition engineering for low-concentration formaldehyde detection - Yunjiang Zhang; Yan Zhang; Junjun Sun; Jianliang Cao; Cong Qin; Yan Wang (Journal of Hazardous Materials, 2025)

Effect of blanching times and drying temperatures on the color, moisture migrations, microstructures, phytochemicals, and flavors of chili pepper (Capsicum annuum L.) - Yongkang Xie; Junjun Geng; Ping Li; Yan Zhao; Junhao Han; Hui Yang; Shina Cao (Food Chemistry, 2025)

Impact of stochastic collisions on cloud droplet number concentration and relative dispersion during Meiyu frontal system - Jingxi Sun; Chunsong Lu; Yan Yin; Sinan Gao; Junjun Li; Yiwei Zhang (Atmospheric Research, 2025)

Alzheimer’s Disease-Derived Outer Membrane Vesicles Exacerbate Cognitive Dysfunction, Modulate the Gut Microbiome, and Increase Neuroinflammation and Amyloid-β Production - Shouchao Wei; Xiaochen Ma; Yating Chen; Junjun Wang; Li Hu; Zhou Liu; Lang Mo; Ning Zhou; Wenrong Chen; He Zhu; Shian Yan (Molecular Neurobiology, 2025)

Hydration and solution properties of fluorescently labeled wheat arabinoxylans following enzymatic hydrolysis - Jieya Wang; Yan Liu; Qingbin Guo; Junjun Li; Liang Zou; Xinzhong Hu (Food Hydrocolloids, 2025)

Distribution characteristics, source analysis and ecological risk assessment of PAHs in tea garden soil in China - Jinzhi Li; Jiantao Xue; Yan Tan; Mingmin Jia; Junjun Feng; Xueqing Feng; Ningguo Zheng; Haoxin Fan; Huaiying Yao (Environmental Research, 2025)

Fish community dynamics following the low-head dam removal and newly installed fish passage in a headstream tributary of Jinsha River, Southwest China - Junjun Tan; Junjian Sun; Yuanyang Wang; Huiwu Tian; Bixin Cheng; Jie Qing; Xin Yan; Gan Sun; Senfan Ke; Giri Raj Kattel; Xiaotao Shi (Science of The Total Environment, 2024)

A review of cleaner production of glass-ceramics prepared from MSWI fly ash - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Junjun Wu; Bin Ding (Journal of Environmental Management, 2024)

Structural disorder Triggered by small organic molecules Boosting δ-MnO2 cathode for Ultra‐Stable aqueous zinc ion batteries - Junjun Tang; Shuan Ma; Yu Jiang; Lufeng Yang; Jie Chen; Xuemin Yan; Bohong Chen; Zhenxiong Huang (Chemical Engineering Journal, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Optimizing growth and antioxidant function in heat-stressed broilers with vitamin C and betaine supplementation - Yan Li; Junjun Yuan; Shiang Sun; Feiyang Ma; Yongjie Xiong; Shaojun He (International Journal of Biometeorology, 2024)

Clusterin is a Potential Therapeutic Target in Alzheimer’s Disease - Nazhakaiti Palihati; Yuanhong Tang; Yajuan Yin; Ding Yu; Gang Liu; Zhenzhen Quan; Junjun Ni; Yan Yan; Hong Qing (Molecular Neurobiology, 2024)

Diversity and influencing factors of microbial communities in rhizosphere and nonrhizosphere soils of tea plant - Junjun Feng; Mingmin Jia; Yan Tan; Hongwen Yue; Xueqing Feng; Ningguo Zheng; Juan Wang; Jiantao Xue (Journal of Soils and Sediments, 2024)

Effects of acetyl groups on the prebiotic properties of glucomannan extracted from Artemisia sphaerocephala Krasch seeds - Haocheng Li; Gongda Wang; Ximei Yan; Xinzhong Hu; Junjun Li (Carbohydrate Polymers, 2024)

Magnetic resonance imaging and deoxyribonucleic acid methylation–based radiogenomic models for survival risk stratification of glioblastoma - Wentao Zhang; Zikang Yan; Jian Peng; Shan Zhao; Longke Ran; Haoyang Yin; Dong Zhong; Junjun Yang; Junyong Ye; Shengsheng Xu (Medical & Biological Engineering & Computing, 2024)

The application of nanopore targeted sequencing for pathogen diagnosis in bronchoalveolar lavage fluid of patients with pneumonia: a prospective multicenter study - Qinqing Lin; Yake Yao; Xi Li; Shanshan Zhang; Huimin Guo; Xiaolong Ma; Wenyu Chen; Chuhui Ru; Limin Wang; Bin Wang; Qiang Ma; Junfei Zhu; et al. (Infectious Diseases, 2024)

Response of growth performance and cecum microbial community to cyclic heat stress in broilers - Junjun Yuan; Yan Li; Shiang Sun; Jiaying Wu; Jin Zhou; Shaojun He (Tropical Animal Health and Production, 2024)

Knowledge, Attitude, and Practice of Breast Cancer Patients Toward Lymphedema Complications: Cross-Sectional Study - Yan Qin; Junjun Lu; Shanze Li; Jie Huang; Wenjing Teng; Yue Wu; Wanqing Chen; Lizhen Wang; Weikang Zhu (Journal of Cancer Education, 2023)

Enhancing sustainable valorization: Harmless synergistic melting treatment for high-value vitreous products from MSWI fly ash and electrolytic manganese residue - Xudong Chen; Yu Tan; Hui Yan; Jun Shi; Bin Ding; Junjun Wu (Waste Management, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Structural and functional neural substrates underlying the concreteness effect - Jing Yan; Wenjuan Li; Tingting Zhang; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Structure and Function, 2023)

Research on Multi-Equipment Cluster Scheduling of U-Shaped Automated Terminal Yard and Railway Yard - Junjun Li; Lixing Yan; Bowei Xu (Journal of Marine Science and Engineering, 2023)
A new layout of the U-shaped automated terminal is more convenient to connect between the terminal and the railway. In this study, a sort of cluster scheduling method for multiple equipment between a U-shaped automated terminal yard and a railway yard is proposed. The innovation points are as follows: (1) Considering that the rail gantry crane (RGC), intelligent guided vehicle (IGV), and double cantilever rail crane (DCRC) usually work in groups, they are grouped and cluster-scheduled. (2) A hybrid integer programming model is established to minimize container transit times, and non-crossing constraints and safe distance constraints are included to reflect complex interactions among terminal equipment. (3) An ADMM (Alternating Direction Method of Multipliers)-based framework is proposed to dualize the hard-edge constraints and break the cluster scheduling problem down into a specific subproblem set of RGCs, IGVs, and DCRCs, and their time cost is iteratively adjusted to improve the solution quality. The experiment results show that the solution of the proposed method, which can effectively avoid IGV conflict, is better than that of the standard Lagrange relaxation (LR) when the number of equipments participating in scheduling increases. This study on multi-equipment cluster scheduling is conducive to improving the collaborative handling and continuous work of terminal equipment, and improving the efficiency of the automated terminal and the sea–rail intermodal transport.

Response of partial nitritation/anammox granules to biodegradable organic input in bacterial community and functions - Feiyue Qian; Yaru Liu; Chenyun Mo; Huan Zhang; Feng Yan; Junjun Gao; Jinlong Zhuang (Journal of Water Process Engineering, 2023)

Modulating interfacial charge distribution of NiSe nanoarrays with NiFe-LDH nanosheets for boosting oxygen evolution reaction - Weiwei Bao; Chunming Yang; Taotao Ai; Junjun Zhang; Lihai Zhou; Yan li; Xueling Wei; Xiangyu Zou; Yong Wang (Fuel, 2023)

Rainfall interception measurements and modeling in a semiarid evergreen spruce (Picea crassifolia) forest - Junjun Yang; Zhibin He; Jianmin Feng; Pengfei Lin; Jun Du; Lingxia Guo; Yufeng Liu; Jialiang Yan (Agricultural and Forest Meteorology, 2023)

The critical role of the orbitofrontal cortex for regret in an economic decision-making task - Tingting Zhang; Qiuzhu Zhang; Jiaqi Wu; Min Wang; Wenjuan Li; Jing Yan; Junjun Zhang; Zhenlan Jin; Ling Li (Brain Structure and Function, 2022)

Numerical model for static chamber measurement of multi-component landfill gas emissions and its application - Haijian Xie; Xinru Zuo; Yunmin Chen; Huaxiang Yan; Junjun Ni (Environmental Science and Pollution Research, 2022)
The quantitative assessment of landfill gas emissions is essential to assess the performance of the landfill cover and gas collection system. The relative error of the measured surface emission of landfill gas may be induced by the static flux chamber technique. This study aims to quantify effects of the size of the chamber, the insertion depth, pressure differential on the relative errors by using an integrated approach of in situ tests, and numerical modeling. A field experiment study of landfill gas emission is conducted by using a static chamber at one landfill site in Xi’an, Northwest China. Additionally, a two-dimensional axisymmetric numerical model for multi-component gas transport in the soil and the static chamber is developed based on the dusty-gas model (DGM). The proposed model is validated by the field data obtained in this study and a set of experimental data in the literature. The results show that DGM model has a better capacity to predict gas transport under a wider range of permeability compared to Blanc’s method. This is due to the fact that DGM model can explain the interaction among gases (e.g., CH 4 , CO 2 , O 2 , and N 2 ) and the Knudsen diffusion process while these mechanisms are not included in Blanc’s model. Increasing the size and the insertion depth of static chambers can reduce the relative error for the flux of CH 4 and CO 2 . For example, increasing the height of chambers from 0.55 to 1.1 m can decrease relative errors of CH 4 and CO 2 flux by 17% and 18%, respectively. Moreover, we find that gas emission fluxes for the case with positive pressure differential ( ∆P in-out ) are greater than that of the case without considering pressure fluctuations. The Monte Carlo method was adopted to carry out the statistical analysis for quantifying the range of relative errors. The agreement of the measured field data and predicted results demonstrated that the proposed model has the capacity to quantify the emission of landfill gas from the landfill cover systems.

Analysis on the hotspot characteristics of bird diversity distribution along the continental coastline of China - Peng Hou; Junjun Bai; Yan Chen; Jing Hou; Jiajun Zhao; Yutiao Ma; Jun Zhai (Frontiers in Marine Science, 2022)
Global climate change and disturbances from human activities lead to habitat loss and changes in habitat quality, resulting in a reduction in biodiversity. The continental coastline of China distributes some cities with highly developed economies and coastal wetlands with rich biodiversity, and both economic development and biodiversity conservation are important topics. In order to clarify the spatial distribution of bird biodiversity in coastal areas, based on the MaxEnt model and GIS spatial analysis, the distribution data of 488 species of birds and 15 environmental variables were used to simulate the suitable distribution areas of birds, and to analyze the spatial distribution and hotspots of bird biodiversity in coastal areas. The main findings of this study are as follows. (1) A total of 488 species in 249 genera of 21 orders and 81 families of birds were involved in the modeling of coastal areas. The main environmental factors affecting the potential distribution of birds in general are: land use, monthly mean diurnal temperature range, and precipitation of the driest month. (2) High value areas of bird richness are distributed in different locations in the four sea areas: In the Bohai Rim region, they are mainly distributed in the Liaohe Estuary Wetland in Liaoning Province, the vicinity of the Yongdingxin River and Haihe River in Tianjin, the eastern part of Tianjin, and the Yellow River and Yellow River Delta Wetland in Shandong Province; In the coastal area of the Yellow Sea, they are primarily found in Kunyu Mountain National Nature Reserve, Laoshan Provincial Nature Reserve in Shandong Province, and Yancheng Wetland Rare Birds National Nature Reserve in Jiangsu Province; In the coastal areas of the East China Sea, they are mainly found at the mouth of the Yangtze River, at the national nature reserve of Dongtan birds on Chongming Island, along the southeastern coast of Zhejiang Province, near the Min River and along the coast of Quanzhou in Fujian Province; In the coastal areas of the South China Sea, they are mainly distributed in the Pearl River Delta wetlands of Guangdong Province, the southeastern coastal areas of the Guangdong-Hong Kong-Macao Greater Bay Area, and the Shiwanda Mountain National Nature Reserve in Guangxi Province. (3) The spatial trends in the distribution of hotspots of birds of national priority protection in coastal areas are generally consistent, but more concentrated than the distribution of all birds. (4) After the high-value areas of bird richness were superimposed with protected areas, it was found that the intersecting area accounted for a small proportion of the protected area, and many areas near the inland had low bird richness. Finally, the findings provide references for bird biodiversity conservation and planning in coastal areas.

Selenium Ameliorates S. aureus-Induced Inflammation in Bovine Mammary Epithelial Cells by Regulating ROS-Induced NLRP3 Inflammasome - Yan Yang; Shenjin Lv; Zhennan Wang; Junjun Liu (Biological Trace Element Research, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Neuroanatomical correlates of self-awareness of highly practiced visuomotor skills - Junjun Li; Zhenglong Lin; Ran Tao; Min Xu; Shihong Kong; Hong-Yan Bi; Yang Yang (Brain Structure and Function, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

OsRhoGAP2 promoter drives inflorescence-preferential expression and confers responses to abiotic stresses in transgenic Arabidopsis - Junjun Huang; Xintian Yan; Jiajia Li; Jia Shi; Jingjing Peng; Jingyao Du; Huiwen Ge; Meina Wang; Wenjing An; Kaijie Wang; Huahua Wang; Weihong Liang (Acta Physiologiae Plantarum, 2019)

Attribution assessment and projection of natural runoff change in the Yellow River Basin of China - Zhe Yuan; Denghua Yan; Zhiyong Yang; Jijun Xu; Junjun Huo; Yanlai Zhou; Cheng Zhang (Mitigation and Adaptation Strategies for Global Change, 2018)

Stability assessment of a new antithrombotic small peptide, Arg-Gly-Asp-Trp-Arg (RGDWR), and its derivative - Lijun Yang; Litao Zhang; Lihong Yan; Haifeng Zheng; Peifen Lu; Junjun Chen; Jie Dai; Haibiao Sun; Yong Xu; Tao Yang (Biotechnology Letters, 2017)

Nitric oxide-mediated cytosolic glucose-6-phosphate dehydrogenase is involved in aluminum toxicity of soybean under high aluminum concentration - Huahua Wang; Junjie Hou; Yan Li; Yangyang Zhang; Junjun Huang; Weihong Liang (Plant and Soil, 2017)

Carnosic acid protects non-alcoholic fatty liver-induced dopaminergic neuron injury in rats - Ting Xu; Junjun Zhou; Jie Zhu; Shuai Zhang; Ning Zhang; Yan Zhao; Chunchun Ding; Xue Shi; Jihong Yao (Metabolic Brain Disease, 2017)

Oxidative Modification and Its Implications for the Neurodegeneration of Parkinson’s Disease - Junjun Zhao; Shuqing Yu; Yan Zheng; Hui Yang; Jianliang Zhang (Molecular Neurobiology, 2017)

Histone acetylation and reactive oxygen species are involved in the preprophase arrest induced by sodium butyrate in maize roots - Qi Zhang; Pu Wang; Haoli Hou; Hao Zhang; Junjun Tan; Yan Huang; Yingnan Li; Jinping Wu; Zhengming Qiu; Lijia Li (Protoplasma, 2017)

Nitrate reductase-mediated nitric oxide production alleviates Al-induced inhibition of root elongation by regulating the ascorbate-glutathione cycle in soybean roots - Huahua Wang; Yan Li; Junjie Hou; Junjun Huang; Weihong Liang (Plant and Soil, 2017)

Involvement of nitric oxide-mediated alternative pathway in tolerance of wheat to drought stress by optimizing photosynthesis - Huahua Wang; Junjun Huang; Yan Li; Changan Li; Junjie Hou; Weihong Liang (Plant Cell Reports, 2016)

Effects of endogenous salicylic acid synthesized through PAL and ICS pathway on baicalin and baicalein accumulation in Scutellaria baicalensis Georgi - Hu Su; Chao Yu; Junjun Shang; Xin Yan; Pengfei Liao; Youlin Zhu; Yanchun Gong; Bin Zeng (Acta Physiologiae Plantarum, 2016)

Comparative analysis of genetic structure in Magnaporthe oryzae isolates from indica and japonica hosts in China - Junjun Shang; Yina Wang; Liu Su; Mansi Luo; Xin Yan; Chao Yu; Youlin Zhu (Journal of General Plant Pathology, 2016)

Exogenous EDDS modifies copper-induced various toxic responses in rice - Junjun Tan; Shibin He; Shihan Yan; Yingnan Li; Hui Li; Hao Zhang; Lin Zhao; Lijia Li (Protoplasma, 2014)

Tissue distribution and expression of signaling lymphocyte activation molecule receptor to peste des petits ruminant virus in goats detected by real-time PCR - Xuelian Meng; Yongxi Dou; Junjun Zhai; Hairui Zhang; Fengchao Yan; Xiaoni Shi; Xuelong Luo; Hui Li; Xuepeng Cai (Journal of Molecular Histology, 2011)